Hymenoptera Complex Associated with Myzus persicae and Hyalopterus spp. in Peach Orchards in Northeastern Spain and Prospects for Biological Control of Aphids - Aparicio, Yahana; Gabarra, Rosa; Riudavets, Jordi; Starý, Petr; Tomanović, Željko; Kocić, Korana; Pujade Villar, Juli; Ferrer Suay, Mar; Cuesta Porta, Victor; Arnó, Judit (Insects, 2019)
Aphids are a serious pest for peach crops. They have traditionally been managed with insecticides, but there is increasing concern about the risk that insecticides pose to both humans and the environment. As a first step to use biological control in aphid management, we conducted a 3-year field survey in northeastern Spain to determine which parasitoids and hyperparasitoids were most prevalent on two aphids, Myzus persicae (Sulzer) and Hyalopterus spp. Koch, the most harmful to peach trees. We collected 11 parasitoid species from M. persicae, with Aphidius matricariae (Haliday) being the most abundant. Two parasitoid species were also collected from Hyalopterus spp., Aphidius transcaspicus Telenga and Praon volucre (Haliday). Hyperparasitoid species overlapped between these aphids but their relative abundances differed. We also discuss the possible impacts of hyperparasitoids on parasitoid populations. Our results suggest that it would be feasible to implement biocontrol methods for aphids in integrated pest management programmes in peach orchards. There are a number of primary parasitoid species associated with these aphids, and the nearby crops and wild vegetation in the vicinity and within the orchards may provide a suitable habitat for them. Additionally, some of them are commercially available and might be usable in augmentative releases.
Keywords: Aphididae; hyperparasitoids; conservation; Aphidiinae; IPM